Identification of Closed Linear Epitopes in S1-RBD and S2-HR1/2 of SARS-CoV-2 Spike Protein Able to Induce Neutralizing Abs - Yoshihiro Watanabe; Natsuko Hosokawa; Misaki Yoshida; Tomoyuki Miura; Mitsuhiro Kawano (Vaccines, 2023)
SARS-CoV-2 has evolved as several variants. Immunization to boost the Ab response to Spike antigens is effective, but similar vaccines could not enhance Ab efficacy enough. Effective Ab responses against the human ACE2 (hACE2)-mediated infection of the emerging SARS-CoV-2 variants are needed. We identified closed linear epitopes of the SARS-CoV-2 Spike molecule that induced neutralizing Abs (nAbs) against both S1-RBD, responsible for attachment to hACE2, and S2-HR1/2, in convalescents and vaccine recipients. They inhibited a pseudo-virus infection mediated by the hACE2 pathway. The epitope sequences included epitopes #7 (aa411-432), #11 (aa459-480) and #111 (aa1144-1161), in S1-RBD and S2-HR2. Epitope #111 was conserved in Wuhan and variant strains, whereas #7 and #11 were conserved in Wuhan carried mutations K417N and S477N/T478K in Omicron BA.4/5. These mutations were recognized by the original epitope-specific Abs. These epitopes in RBD and HR2 neither contained, nor overlapped with, those responsible for the antibody-dependent enhancement of the SARS-CoV-2 infection. The sublingual administration of multiple epitope-conjugated antigens increased the IgG and IgA Abs specific to the neutralizing epitopes in mice pre-immunized subcutaneously. The findings indicated that S1-RBD and S2-HR2 epitopes were responsible for pseudo-virus SARS-CoV-2 infections and that sublingual boosts with multiple epitope-conjugated antigens could enhance the protection by nAbs of IgG and IgA against infection by a wide range of variants.